OPTIMIZING THE UTILIZATION OF THE POTENTIAL OF LOCAL NATURAL RESOURCES THROUGH THE EMPOWERMENT OF COCONUT FARMERS TO INCREASE THE INCOME OF THE PEOPLE OF SELAYAR REGENCY - warda warda; Arif Arif (Inovbiz: Jurnal Inovasi Bisnis, 2022)
Coconuts in the Selayar Islands Regency have an important role as a source of community income and also as a source of regional foreign exchange, in fact coconut farmers are still not prosperous from a long-running business. This study aims (1) to find out what empowerment efforts are given to coconut farmers in Tambolongan Village, Bontomatene District, Selayar Islands Regency. (2) To find out the obstacles faced by coconut farmers in increasing income in Tambolongan Village, Bontomatene District, Selayar Islands Regency. This research was conducted on coconut farmers in Tambolongan Village, Bontomatene District, Selayar Islands Regency. Sampling was carried out randomly on coconut farmers who were then interviewed directly using a list of questions. The data obtained were then analyzed using qualitative descriptive analysis. The results of the researcher's analysis show that efforts to empower coconut farmers by the local government are almost non-existent. Coconut farmers' income from production is still low. Coconut farmers' income from production is still low. The obstacles faced by coconut farmers include low education, not being able to see existing business opportunities, and limited capital being one of the obstacles to the slow development of coconut farming business.